social fund for development : annual report 1994 (World Bank, 1994)
This eighteenth annual World Development Report assesses what a more market-driven and integrated world means for workers. It asks which development strategies best address workers' needs, and what domestic labor market policies can do to establish a more equitable distribution of income, greater job security, and higher workplace standards, while preserving and indeed enhancing the efficiency of labor markets. The Report concludes that global integration holds out the prospect of tremendous future gains for the world's work forcebut no guarantees. Sound domestic and international policies are indispensable for realizing the promise of a prosperous, integrated global workplace. Policies that rely on markets while avoiding or correcting market failures, that invest in people, that provide a supportive environment for family farms as well as emerging industrial and services sectorsall these are good for workers. Governments continue to exercise important functions: building and maintaining the social framework within which workers, unions, and firms interact to set wages and working conditions; supporting workers who are hurt when industries or whole economies suffer major shocks; and defending the rights of the most vulnerable workers, whether they be child laborers victimized by exploitation, or women or ethnic minorities suffering from discrimination. In those economies that are less prepared to face global competitionin particular, those emerging from central planningpublic action has a particularly important role in promoting labor mobility, easing the cost of transition, and reaching those left out. This Report includes the World Development Indicators, which offer comprehensive, current data on social and economic development in more than 200 countries and territories. The Indicators are also available on diskette. An Appendix to the Report provides additional statistics on labor.